2014
DOI: 10.1155/2014/968402
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Ga(III) by Raw and Alkali Treated Citrus limetta Peels

Abstract: Alkali treated Citrus limetta peels were used for recovery of Ga(III) from its aqueous solution. The raw and alkali treated peels were characterized for functional groups. The efficiency of adsorption increased from 47.62 mg/g for raw peels to 83.33 mg/g for alkali treated peels. Between pH 1 and 3, the adsorption increased and thereafter decreased drastically. The adsorption followed pseudosecond order kinetics and Langmuir isotherm gave the best fit for the experimental data. Desorption studies showed 95.28%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Alkali-modification both significantly increased the (%) biosorption of copper and the pH of the water as compared to the pristine biosorbent and the carbonized biosorbent. A similar observation was obtained from the study of [26] where the alkali-treated Citrus limetta peels showed enhanced adsorption capacity in the recovery of Gallium (III). As discussed by [27], this can be explained by the removal of surface impurities present on the biosorbent particles and exposure of the active binding sites for metal adsorption after the solubilization of hemicellulose and pectin embedded in the cell walls as an effect of the treatment with Sodium hydroxide (NaOH).…”
Section: *Created With References To [37 27]supporting
confidence: 84%
See 2 more Smart Citations
“…Alkali-modification both significantly increased the (%) biosorption of copper and the pH of the water as compared to the pristine biosorbent and the carbonized biosorbent. A similar observation was obtained from the study of [26] where the alkali-treated Citrus limetta peels showed enhanced adsorption capacity in the recovery of Gallium (III). As discussed by [27], this can be explained by the removal of surface impurities present on the biosorbent particles and exposure of the active binding sites for metal adsorption after the solubilization of hemicellulose and pectin embedded in the cell walls as an effect of the treatment with Sodium hydroxide (NaOH).…”
Section: *Created With References To [37 27]supporting
confidence: 84%
“…The shifting of the peaks of carbonyl (from 1412 cm -1 to 1420 cm -1 ) and of carboxylates (from 1366 cm -1 to 1373 cm -1 ) after the modification of the biosorbent particularly after alkali treatment indicates interaction of the biomass to the sodium ions. Also, the peak for ester at 1728 cm -1 disappeared after the alkali modification and carbonization, as mentioned by [26] alkali treatment facilitates the conversion of esters present in the pristine biosorbent into carboxylic acid in the process of base-promoted ester hydrolysis/saponification, which is then converted to carboxylate [37]. On the other hand, peak at 1412 cm -1 for carboxylate disappeared only after carbonization.…”
Section: Discussion 41 Characterization Of Surface Functional Groups Atr-ftirmentioning
confidence: 99%
See 1 more Smart Citation